Preparation for Indonesian Election 2024: Women's Participation in Political Contest - Linayati Lestari; Aqil Teguh Fathani; Zahrul Akmal Damin (Journal of Governance, 2023)
This article focuses on the preparation and participation of Indonesian female candidates in the Riau Archipelago Province's 2024 political contest. Why women participate in political parties and legislative seats at such a low rate is a big question. The Mix Method research to find the best results elaboration. In-depth interviews were conducted with six political party leaders, and 120 questionnaires were distributed to each party. Each party was given 20 questionnaires containing the same questions. The traditional political environment is still the main reason for women's participation, and this will also be the case in the 2024 elections. The primary reason is their need for more involvement in election recruitment, nomination, and candidacy. The emphasis is very much on the patriarchal system, and women's families and personal environments are inadequate. Aside from that, there is a limit: the stigma of women in politics is only significant as a background player. Existing regulations are formalities; each party has its own method of conditioning existing regulations. There must be firmness in the system of 30% quotas for women, or even better, a strategic way for them to want to participate in the elections of 2024 and beyond.